Birch Reduction of Arenes as an Easy Entry to γ‐Spirolactones. Issue 46 (16th November 2021) - Krüger, Tobias; Bramborg, Andrea; Kelling, Alexandra; Sperlich, Eric; Linker, Torsten
Abstract: A convenient method for the synthesis of γ‐spirolactones in only 2–3 steps is described. Birch reduction of inexpensive and commercially available aromatic carboxylic acids in the presence of ethylene oxide affords hydroxy acids, which undergo direct lactonization during work‐up. Suitable precursors are methyl‐substituted benzoic acids, naphthoic, and dicarboxylic acids. Subsequent hydrogenation proceeds smoothly with Pd/C as catalyst and saturated γ‐spirolactones are isolated in excellent yields and stereoselectivities. Thus, up to 3 new stereogenic centers can be constructed as sole diastereomers from achiral benzoic acids. Furthermore, it is possible to control the degree of saturation with Raney nickel or Wilkinson's catalyst to obtain products with 1 double bond. Overall, more than 30 new γ‐spirolactones have been synthesized in analytically pure form. Abstract : Birch reduction of arene carboxylic acids in the presence of ethylene oxide affords γ‐spirolactones directly after acidic workup. Subsequent catalytic hydrogenation allowed to control the degree of saturation by variation of the catalyst. Thus, more than 30 new γ‐spirolactones have been synthesized from inexpensive starting materials in high yields.